Improved photoelectrochemical hydrogen production performance of reduced graphene oxide-cadmium zinc sulfoselenide photoelectrodes prepared by a Facile In-situ Electrosynthesis method - BUDAK, ÖZLEM; KOCA, ATIF (My University, 2023)
Cadmium zinc sulfoselenide, CdZnSSe, and reduced graphene oxide-cadmium zinc sulfoselenide (RGO)-CdZnSSe composite-based photoelectrodes are fabricated using a facile, simultaneous co-electrodeposition by repetitive cyclic voltammetric (rCV) for the first time in literature. With this method, CdZnSSe particles are homogeneously decorated among the RGO sheets by controlling the composition of the composite structure and the film thickness with rCV. Photoelectrochemical, optical, and structural properties of photoelectrodes are evaluated to investigate their usability in photoelectrochemical hydrogen evolution. Decorating Cd0.8Zn0.2S0.2Se0.8 among RGO sheets leads to a slight red-shift of the absorption edge because of the less transparency of fabricated photoelectrode which decreases the band gap of composites. Among all Cd0.8Zn0.2SxSe1-x (x = 0.0, 0.2, 0.5, 0.8, 1.0) photoelectrodes, Cd0.8Zn0.2S0.2Se0.8 demonstrates the sharp rise in photocurrent density (4.08 mA cm−2). Decorating Cd0.8Zn0.2S0.2Se0.8 with RGO at an optimum composition jumps the photocurrent density up to 5.00 mA cm−2 in addition to the improved stability. The long-term stability of RGO(0.25)-Cd0.8Zn0.2S0.2Se0.8 is reported as 89.8% at the end of the 48th hour. The applied bias photon to current efficiency (ABPE) and Faradaic efficiency are obtained as 3.07% and 89.9%. Enhanced photoelectrochemical performance indicates the superiority of the proposed rCV technique for the fabrication of well-controlled photoelectrodes consisting of RGO[sbnd]CdZnSSe composites.
Keywords: Kimya Mühendisliği ve Teknolojisi; Kimya; Fizikokimya; Elektrokimya; Temel Bilimler; Mühendislik ve Teknoloji; Chemical Engineering and Technology; Chemistry; Physical Chemistry; Electrochemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; MÜHENDİSLİK, KİMYASAL; ELEKTROKİMYA; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; CHEMISTRY; ENGINEERING, CHEMICAL; ELECTROCHEMISTRY; Genel Kimya Mühendisliği; Fizik Bilimleri; General Chemical Engineering; Physical Sciences; Cadmium zinc selenide; Cadmium zinc sulfide; Cyclic voltammetry; Electrodeposition; Reduced graphene oxide